Emerging mechanisms and functions of inflammasome complexes in teleost fish - Chang, Ming Xian (Frontiers in Immunology, 2023)
Inflammasomes are multiprotein complexes, which are assembled in response to a diverse range of exogenous pathogens and endogenous danger signals, leading to produce pro-inflammatory cytokines and induce pyroptotic cell death. Inflammasome components have been identified in teleost fish. Previous reviews have highlighted the conservation of inflammasome components in evolution, inflammasome function in zebrafish infectious and non-infectious models, and the mechanism that induce pyroptosis in fish. The activation of inflammasome involves the canonical and noncanonical pathways, which can play critical roles in the control of various inflammatory and metabolic diseases. The canonical inflammasomes activate caspase-1, and their signaling is initiated by cytosolic pattern recognition receptors. However the noncanonical inflammasomes activate inflammatory caspase upon sensing of cytosolic lipopolysaccharide from Gram-negative bacteria. In this review, we summarize the mechanisms of activation of canonical and noncanonical inflammasomes in teleost fish, with a particular focus on inflammasome complexes in response to bacterial infection. Furthermore, the functions of inflammasome-associated effectors, specific regulatory mechanisms of teleost inflammasomes and functional roles of inflammasomes in innate immune responses are also reviewed. The knowledge of inflammasome activation and pathogen clearance in teleost fish will shed new light on new molecular targets for treatment of inflammatory and infectious diseases.